Proceedings of the 9th International Symposium on Antennas, Propagation and EM Theory 2010
DOI: 10.1109/isape.2010.5696435
|View full text |Cite
|
Sign up to set email alerts
|

Truncated tip triangular microstrip patch antenna

Abstract: This paper presents a design of triangular microstrip antenna with truncated tip and experimentally studied on Ansoft Designer v-2.2.0 software. This design technology is achieved by cutting all three tips of the triangular microstrip antenna and placing a single coaxial feed. Triangular patch antenna is designed on a FR4 substrate of thickness 1.6 mm and relative permittivity of 4.4 and mounted above the ground plane at a height of 6 mm. Bandwidth as high as 11.07% are achieved with stable pattern characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The design has demonstrated that a single probe feed square patch antenna with Graphene structure can be used to form an antenna with impedance bandwidth of 65.67% working in Wi-max wireless communication system with resonant frequency 1.1667 GHz [11]. These modern communication systems require antennas with broadband and/or multi-frequency operation modes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design has demonstrated that a single probe feed square patch antenna with Graphene structure can be used to form an antenna with impedance bandwidth of 65.67% working in Wi-max wireless communication system with resonant frequency 1.1667 GHz [11]. These modern communication systems require antennas with broadband and/or multi-frequency operation modes.…”
Section: Discussionmentioning
confidence: 99%
“…The microstrip patch antennas are broadly used in satellite and missile applications due to its advantages of conformal to planar and nonplanar surfaces [10]. The conformal patch antenna consists of parallel electric conductors, separated from the flexible dielectric material and can be fabricated using thin film deposition and nano lithography techniques [11]. The low dielectric permittivity material is needed for improving the radiation efficiency in the desired direction [12].…”
Section: Introductionmentioning
confidence: 99%
“…In antenna fabrication, a 50 Ω SMA connector and probe feed technique have been used. The main advantage of this technique is that the feed can be placed at any place in the patch to match with its input impedance [7]. Simulation and design of antenna was done using CST Microwave Studio software, and then the antenna has been fabricated in laboratory by using chemical etching process [17].…”
Section: Antenna Designmentioning
confidence: 99%
“…The MPA is extensively utilized in both commercial and government sectors, particularly in wireless communication and mobile radio technologies. 1 Despite its widespread use, antenna design encounters numerous challenges. The ultra-wideband (UWB) antenna faces challenges like the radiation emitted from antennas not only impacts polarization characteristics but also diminishes radio efficiency.…”
Section: Introductionmentioning
confidence: 99%